PKM - PENGUSAHA ARANG TEMPURUNG KELAPA DESA BANTAN AIR KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU - Abdul Haris Salam; Syahrizal Syahrizal (Universitas Lancang Kuning, 2018)
Bantan Air Village, which is part of Bantan District, Bengkalis Regency, has been established by two SMEs and is engaged in processing coconut shells into charcoal. Both of these MSMEs already have burning stoves but have the same problem, namely the smoke produced from burning coconut shells is released into the air without further treatment. The smoke that is discharged can of course disrupt the health of workers or the community around the place of business. Thus, it is necessary to apply more applicable science and technology to reduce smoke pollution and even convert the smoke waste into something that has a selling value. The proposer and the two partners have agreed to solve this problem, namely the manufacture of condensers to turn smoke into liquid, so that the aim of reducing pollution and increasing revenue can be achieved. This PKM activity begins with a preliminary survey to the location of partners and determines the solution to the problem, followed by the making of a condenser, provides training in how to operate equipment, care and guidance. The output target of this PKM has been achieved by producing a condenser to reduce smoke from the burning of coconut shells and produce products in the form of liquid smoke that is ready to sell. In addition, the community and MSME workers have also been given counseling and training in the use of condensers so that the knowledge and skills of workers can increase